2021
DOI: 10.1002/eom2.12107
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics release from victuals packaging materials during daily usage

Abstract: Plastic packaging materials are widely used because of their advantages of light weight, low cost, and convenience, especially as victuals packaging materials. Approximately 146 million metric tons of plastics were used for packaging in 2015, but most of these plastics had already been discarded and followed by serious white pollution. What's worse, the victuals packaging materials, especially polystyrene (PS) foam containers, can release microplastics (MPs) during daily usage. Through the combination of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 45 publications
(48 reference statements)
2
13
0
Order By: Relevance
“…Microplastics have been one of the potential threats to human health, especially the use of plastic products directly in contact with food and beverages, making microplastics more likely to be ingested by humans. [5] The most commonly used polypropylene (PP) plastic straws are immersed in deionized water at their daily use temperature to simulate usage environment, exploring the risk of microplastics release. As a result, microplastics with different irregular shapes can be observed in the solution under an optical microscope (Figure S1, Supporting Information).…”
Section: Microplastic Analysis and Fabrication Strategy Of Microplast...mentioning
confidence: 99%
See 1 more Smart Citation
“…Microplastics have been one of the potential threats to human health, especially the use of plastic products directly in contact with food and beverages, making microplastics more likely to be ingested by humans. [5] The most commonly used polypropylene (PP) plastic straws are immersed in deionized water at their daily use temperature to simulate usage environment, exploring the risk of microplastics release. As a result, microplastics with different irregular shapes can be observed in the solution under an optical microscope (Figure S1, Supporting Information).…”
Section: Microplastic Analysis and Fabrication Strategy Of Microplast...mentioning
confidence: 99%
“…recent research has found that plastic products continuously release microplastics during their lifespan, which can be directly or indirectly ingested by human beings, causing potential detrimental threats to human health. [4][5][6][7][8] Upon noting the above phenomena, great efforts have been made on exploring new materials to replace plastic straws and address the environmental problems over the years. [9][10] After continuously selected, current alternatives to plastic straws mainly include biodegradable polymers and natural plant-based straws.…”
mentioning
confidence: 99%
“…Movie S1 shows that the film does not form any destructive creases after being fully folded and can be restored to intactness after being rolled. As we all know, petrochemical-based plastics are widely used as films, but they are so difficult to degrade that they pose a potential threat to the environment and even human health. Instead, the multiscale film is fully biodegradable and has higher strength and modulus than those of petrochemical-based plastic films (Figure c). These superior mechanical properties mentioned above indicate its huge application potential to replace plastics in specific applications such as flexible electronic devices.…”
mentioning
confidence: 99%
“…[ 1–3 ] These PCPs, however, are non‐renewable and non‐biodegradable and, because of low‐recycling rates and poor waste management, pose a considerable threat to the environment, wildlife, and human health. [ 4–6 ] In order to alleviate the pollution caused by PCPs, efforts have been made to develop renewable, biodegradable, and eco‐friendly bio‐plastics (BPs) from materials such as cellulose, lignocellulose, polylactic acid, polyhydroxyalkanoates, starch, and proteins. [ 7–10 ] Production of BPs from different biomass resources (largely lignin, cellulose, and hemicellulose) [ 11 ] reduces reliance on fossil fuels and also cuts greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%